(untitled) (Journal of the College of Basic Education, 2024)
The copper nanoparticles Cu NPs were successfully prepared via laser triggering wire explosion technique at different explosion voltages (4, 5 and 7 KV). It was observed through atomic force microscopy examinations that the prepared powders are highly homogeneous and contain agglomerations resembling regularly distributed protrusions and that the homogeneity increases with increasing explosion voltage. The examination of the fourier transform infrared spectroscopy showed bonds and functional groups belong to CuO and Cu2O. Antifungal activity tests showed the efficiency of the prepared powders in eliminating Candida albicans, especially the Cu nanopowder prepared at 7KV and a concentration 200 µg/mL.